Highly Selective Continuous Gas‐Phase Methoxycarbonylation of Ethylene with Supported Ionic Liquid Phase (SILP) Catalysts. Issue 10 (10th April 2017) - Khokarale, Santosh G.; García‐Suárez, Eduardo J.; Fehrmann, Rasmus; Riisager, Anders
Abstract: Supported ionic liquid phase (SILP) technology was applied for the first time to the Pd‐catalyzed continuous, gas‐phase methoxycarbonylation of ethylene to selectively produce methyl propanoate (MP) in high yields. The influence of catalyst and reaction parameters such as, for example, ionic liquid loading, metal concentration, and ligand loadings was studied, and in particular the SILP catalyst activity and stability was found to be strongly dependent on the ligand to metal ratio. Abstract : It′s all in the ratio : Supported ionic liquid phase (SILP) technology was applied to the Pd‐catalyzed continuous, gas‐phase methoxycarbonylation of ethylene to selectively produce methyl propanoate in high yields. Studying the influence of catalyst and reaction parameters showed that the SILP catalyst activity and stability was strongly dependent on the ligand to metal ratio.